"O arqueólogo Frederico Barata": a coleção e o colecionador no Museu Paraense Emílio Goeldi - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2004)
The present work is the continuation of a previous one entitled "A current study of Tapajonic archeological collections: analysis and description of the Townsend and Frederico Barata collections". Here we turn exclusively to the Frederico Barata collection, addressing two aspects: the historical, seeking to explore the image of Frederico Barata as an archaeologist; and the archaeological, which includes the classification, reorganization, and technical analysis of the fragments of the collection. For the first, a bibliographic and documental survey was carried out, while for the second we adopted the criteria established by the Project for the Reorganization of the Archaeological Collection of the Museu Paraense Emílio Goeldi (1999), and had as reference the work done by Guapindaia (1993) and Gomes (2001). Thus, Barata's publications (0950, 1951, 1952a, 1952b, 1953) were evaluated in order to verify their scientific value, and the documents researched in the Emílio Goeldi Museum Archives helped us to understand the prestige that Barata had in the scientific community. Regarding the work carried out in MPEG's "Mario Simões" Technical Reserve - where the collection is located - all the material of the collection was reorganized and classified according to form and origin, and thus we were able to quantify and catalog the fragments of the collection. Unfortunately it was not possible to finalize the analysis of the material due to the grandiosity of this collection. Thus, we can see that Frederico Barata's archaeological activity was not only as a collector, as his non-systematic excavations yielded several significant articles for Amazonian archaeology. Barata was also involved in some activities at MPEG, for example as a member of the institution's Editorial Board in the late 1950s. Finally, this collection, which has been properly contextualized by its judicious collector, can still provide the basis for several articles and monographs.
"The archaeologist Frederico Barata": the collection and the collector at the Museu Paraense Emílio Goeldi
Keywords: Arqueologia Amazônica; Colecionamento; Frederico Barata; CNPQ::CIENCIAS HUMANAS::ARQUEOLOGIA